The (In) famous English Language Policy in Pesantren: What We Already Know and What Remains Unknown - Rahman, Fadhlur; Al-Nahdi, Ali; Zurriyati, Zurriyati (Idarah (Jurnal Pendidikan dan Kependidikan), 2023)
The development of English language instruction ought to align to a well-established educational system that aims to produce students with proficient English language skills. Pesantren, which are educational a institutions that are well-known for their capacity to provide high-quality English language instruction, serve as an illuminating study in this context. This study investigates the goals, practical implementations, and challenges associated with English language instruction in pesantren. In this study, researchers used triangulation to boost the validity and reliability of the findings in investigating English language instruction in pesantren. By combining several data sources, such as document analysis and a semi-structured interview, researchers may construct a cohesive and comprehensive picture of the research subject. Additionally, it investigates the intricate relationship between the various factors that influence students' command of the English language. English language teaching and learning in pesantren operate in a multifaced practices, with each component fulfilling specific roles and functions that are tightly aligned with the overarching goal of English learning. Since each component fulfills a different set of roles and functions, students are able to not only acquire the necessary linguistic competence but also develop effective communication skills, which enables them to flourish in the interconnected and globalized world of today. The interdependence of all facets of teaching English as a foreign language is painstakingly orchestrated, and institutional conditions provide a stable and dependable foundation for this. This study sheds light on the complexities of English language instruction in pesantren and emphasizes the importance of continuous reflection on the purpose of English by examining these key aspects.